Determination of beryllium in solid samples by flame atomic absorption spectrometry after preconcentration on activated carbon - Yaman, Mehmet; Avci, Hatim (Japan Soc Analytical Chemistry, 2006)
It is generally supposed that the preconcentration procedure is used for the determination of metal concentrations under the sensitivity of the measurement method. This study showed that preconcentration is also need for the beryllium (Be) concentration over the sensitivity of atomic absorption spectrometry. For this purpose, a simple and selective method for the determination of Be in solid samples is modified. The method is based on the preconcentration of the complexes of beryllium-acetylacetone plus morin, oxine, PAN and PAR on activated carbon at different pH values. The adsorbed beryllium was eluted with aqua regia and measured by flame atomic absorption spectrometry (FAAS). Recoveries of up to 85% were achieved. For removing chemical interferences and applying the method to Be determination in solid samples, the masking studies and reproducibility were examined. The detection limit was found to be 0.12 ng mL(-1). The relative sandard deviations (RSD) were found to be 8% for 60 mL of 10.0 ng mL(-1) using 10 replicate enrichment procedures. Beryllium concentrations in the studied solid samples were found in the range of 0.28 - 3.95 mg kg(-1).
Keywords: Spectrophotometric Determination; Drinking-Water; Trace Amounts; Enrichment; Vanadium; Lead; Vegetables; Nickel; Speciation; Matrices